Spontaneous Retroperitoneal Hematoma in COVID-19 Severe Pneumonia–Dual-phase Multidetector Computed Tomography Angiogram and Role of Radiologist - Vikash Kumar Gupta; Buthaina Mohammad Alkandari; Wasif Mohammed; Mohsen Ahmed Abdelmohsen; Mohammad Gaber Abdullah Mohammad (Journal of Clinical Interventional Radiology ISVIR)
Studies available in the literature have shown alterations in blood coagulation tests in severe cases of COVID-19 pneumonia, with a significant risk of venous thromboembolism (VTE). Since microvascular thrombosis is a well-known fact in COVID-19 disease, requiring therapeutic anticoagulation, low-molecular weight heparin (LMWH) in prophylactic dose is a part of the clinical management of hospitalized COVID-19 patients. In this scenario, we describe three cases of abdominal spontaneous retroperitoneal hematoma (SRH) in hospitalized reverse transcriptase-polymerase chain reaction (RT-PCR)-confirmed COVID-19 patients.